Low-dose apatinib combined with neoadjuvant chemotherapy in the treatment of early-stage triple-negative breast cancer (LANCET): a single-center, single-arm, phase II trial. (August 2022) - Yang, Ciqiu; Zhang, Junsheng; Zhang, Yi; Ji, Fei; Chen, Yitian; Zhu, Teng; Zhang, Liulu; Gao, Hongfei; Yang, Mei; Li, Jieqing; Cheng, Minyi; Wang, Kun
Background: Antiangiogenic therapy combined with chemotherapy could improve pathological complete response (pCR) for breast cancer. Apatinib is an oral tyrosine kinase inhibitor that selectively inhibits vascular endothelial growth factor receptor 2. We assessed the efficacy and safety of apatinib combined with standard neoadjuvant chemotherapy in patients with triple-negative breast cancer (TNBC). Materials and methods: This single-arm, phase II study enrolled patients aged 18–70 years with previously untreated stage IIA-IIIB TNBC. Patients received oral apatinib at a dose of 250 mg once daily and intravenously docetaxel every 3 weeks for four cycles, followed by epirubicin plus cyclophosphamide every 3 weeks for four cycles. The primary endpoint was the pCR rate in the breast and lymph nodes. Secondary endpoints included objective response rate, event-free survival (EFS), overall survival (OS), and safety. Results: In all, 31 patients were enrolled, and the median follow-up time was 22.9 months (range: 10.1–41.6 months). The pCRs in both breast and lymph nodes were achieved in 17 [54.8%; 95% confidence interval (CI): 36.0–72.7] of 31 patients. Objective responses were achieved in 29 patients (93.5%; 95% CI: 78.6–99.2), and disease control was achieved in 31 patients (100%; 95% CI: 88.8–100.0). The 2-year EFS and 2-year OS were 90.9% and 94.4%, respectively. The five most common treatment-related adverse events were fatigue (51%), hypertension (41%), anorexia (39%), hand–foot syndrome (35%), and diarrhea (32%). Few grade 3 or more adverse events were observed. Conclusion: The combination of apatinib with docetaxel followed by epirubicin plus cyclophosphamide showed excellent efficacy and manageable toxicities; and further randomized controlled phase III trials are warranted. Trial registration: This trial was registered with ClinicalTrials.gov (NCT03243838) on 5 August 2017.